Why is it so rare and random to find pyre sites? Two cremation experiments to understand the characteristics of pyre sites and their investigational possibilities - Fülöp, Kristóf (Dissertationes Archaeologicae, 2019)
The cremation rite is well-defined in space and time as it is the central part of a series of complex ritual events. Although it is one of the most significant and representative elements of the funeral, yet we know very little about it due to its destructive nature, the scarcity of pyre sites and the indirect character of cremated bones and artefacts found in graves. The two experimental cremations presented in this article, on the one hand, address this rare occurrence of pyre sites. On the other hand, by the detailed documentation of the cremation process and the formation of pyre sites, it is possible to examine in detail several new issues related to the pyre sites. Thus, the shape, orientation, dimension, and structure of the funeral pyre, as well as some moments of the cremation are discussed in detail. Furthermore, the representation of the body and pyre goods after the pyre’s burndown, the movement of artefacts during burning, and the watering of pyre remains, as well as the problem of the mixture are also examined. At the same time, the experimental observations also draw attention, besides the investigational possibilities, to the archaeological limitations of pyre sites.